The pale horseman [compact disc, unabridged] - Cornwell, Bernard (Cornwell, Bernard. Last kingdom., 2015)
The Vikings want to finish England. They assemble the Great Army, whose one ambition is to conquer Wessex. Dispossessed young nobleman Uhtred has no love for King Alfred. Yet fate, as Uhtred learns, has its own imperatives, and when the Vikings attack out of a wintry darkness to shatter the last English kingdom, Uhtred finds himself at Alfred's side.